Pretrial Release of Latino Defendants (2008) - David Levin (My University, 2016)
The decision to detain or release a defendant before trial has significant ramifications for the person standing trial. Persons who are denied release tend to more likely be convicted of a felony, be sentenced to jail versus fined, and sentenced to prison versus jail (Demuth, 2003; Spohn, 2000). To date, research that considers what specific factors affect the probability of pretrial release has focused primarily on individual level defendant characteristics (Demuth, 2003; Demuth & Steffensmeier, 2004). In this report, Pretrial Justice Institute (PJI) 1) examines the impact of jurisdiction demographics on pretrial release; and 2) controls for alternate jurisdiction level influences on pretrial decision-making e.g., court caseload rates, prosecutor screening of cases, local jail capacity) which pretrial policy analyses have not previously controlled for. The research questions of this report are:(1) Are Latino defendants less likely to receive pretrial releases than non-Latino defendants?(2) Are Latino defendants in counties where the Latino population is rapidly increasing less likely to receive pretrial releases than Latino defendants in counties where the Latino population is not rapidly increasing?